2010
DOI: 10.1128/jcm.01897-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Polyurethane Foam to Nylon Flocked Swabs for Collection of Secretions from the Anterior Nares in Performance of a Rapid Influenza Virus Antigen Test in a Pediatric Emergency Department

Abstract: Rapid antigen testing of upper respiratory secretions collected with various swab types is often utilized for laboratory diagnoses of influenza virus infection. There are limited data on the effects of swab composition on test performance. This study compared the performance of the Quidel QuickVue Influenza A؉B test on secretions from the anterior nares when a polyurethane foam swab was used for collection to that when a nylon flocked swab was used for collection. One hundred subjects who presented to a pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
27
1
Order By: Relevance
“…The objective of this study was to evaluate the clinical sensitivity and specificity of the Alere i influenza A&B test versus PCR results from residual frozen nasopharyngeal (NP) swab specimens eluted in UTM (NP UTM) from Rhode Island Hospital (RIH) patients. Evaluation of NP UTM specimens is appropriate, as it is a common respiratory sample collection method for many laboratories, since it allows for subsequent testing without the need to collect additional samples from the patient (6,7).…”
mentioning
confidence: 99%
“…The objective of this study was to evaluate the clinical sensitivity and specificity of the Alere i influenza A&B test versus PCR results from residual frozen nasopharyngeal (NP) swab specimens eluted in UTM (NP UTM) from Rhode Island Hospital (RIH) patients. Evaluation of NP UTM specimens is appropriate, as it is a common respiratory sample collection method for many laboratories, since it allows for subsequent testing without the need to collect additional samples from the patient (6,7).…”
mentioning
confidence: 99%
“…With PCR as the gold standard, viral culture carried out at the UHL NHS Trust laboratory had a sensitivity of just 21.6% (95% CI 13.5% to 31.6%), which, although similar to the sensitivity reported by the Portuguese national surveillance network, during the 7-year period 1992-93 to 1998-99, 146 is suboptimal in comparison with sensitivities of 61-96% reported in nine studies 90,91,[147][148][149][150][151][152][153] (Table 24) that were identified for the systematic review and meta-analysis of POCTs for influenza (see Chapter 6). However, the sensitivity of viral culture was similar to that of the Quidel POCT (24.4%, 95% CI 16% to 34.6%).…”
Section: Discussionmentioning
confidence: 63%
“…Scansen et al 90 compared the performance of the Quidel QuickVue Influenza A + B test on secretions from the anterior nares when a polyurethane foam swab was used for collection to that of a nylon flocked swab. The QuickVue test was positive for 40 foam and 30 flocked swabs, for sensitivities of 71% and 54%, respectively, a difference that achieved statistical significance.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…Two relatively recent notable technologies are the use of flocked swabs and FTA cards (Whatman Inc. Whatman Plc, Maidstone, Kent UK). Flocked swabs are composed of a nylon material that is claimed to have superior capture and release characteristics compared with conventional swabs, thus improving sensitivity by increasing the amount of analyte in the sample (Daley et al, 2006;Dalmaso et al, 2008;Scansen et al, 2010). FTA cards have probably had the greatest impact on sample collection and transport of any technology in past decade.…”
Section: E Spackmanmentioning
confidence: 98%